Consumer cosmopolitanism: Review and replication of the CYMYC scale - Riefler, Petra; Diamantopoulos, Adamantios (Journal of business research, 2009)
Extant marketing literature mainly focuses on explaining why consumers might prefer domestic products and refrain from buying foreign products but, however, is weak in explaining why consumers might intentionally opt for foreign products. Against this background, consumer cosmopolitanism has gained increasing attention as a potentially relevant consumer characteristic for explaining foreign product preference and choice. However, empirical evidence on the impact of consumer cosmopolitanism on consumption behavior remains scarce. This paper identifies the absence of an appropriate measurement instrument as a main reason for this lack of empirical studies by providing (a) a review of cosmopolitanism scales used in other research fields, and (b) a replication with extensions study of the CYMYC scale, the only consumer cosmopolitanism scale currently available. The findings highlight a need for a new scale to measure the consumer cosmopolitanism construct. To stimulate further research in this direction, the paper proposes a conceptual definition of consumer cosmopolitanism along with a nomological network to guide the scale development process.